2019
DOI: 10.1371/journal.pbio.3000201
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of FOXD1 by YAP alleviates senescence and osteoarthritis

Abstract: Cellular senescence is a driver of various aging-associated disorders, including osteoarthritis. Here, we identified a critical role for Yes-associated protein (YAP), a major effector of Hippo signaling, in maintaining a younger state of human mesenchymal stem cells (hMSCs) and ameliorating osteoarthritis in mice. Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR associated protein 9 nuclease (Cas9)-mediated knockout (KO) of YAP in hMSCs resulted in premature cellular senescence. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 75 publications
3
102
0
Order By: Relevance
“…We found 737 significantly downregulated genes in the AB uninjured group compared to the VEH uninjured group. These genes included regulators of skeletal development ( Alpl [ 37 ], Col6a1 [ 54 ], Col6a2 [ 55 ], Sox9 [ 37 ], Sox11 [ 56 ], and Wnt9a [ 57 ]), Hippo signaling ( Tead1 , Tead4 [ 58 ], and Yap1 [ 59 ]), muscle contraction ( Myh8 , Myh2 , and Myom2 ), and inflammatory response ( Tlr5 [ 60 ], Ccl8 [ 61 ], Cxcl13 [ 37 ], C5ar1 [ 62 ], Cxcr1 [ 63 ], and Foxo6 [ 64 ]). Inflammatory gene comparison between AB injured and uninjured groups compared to the corresponding VEH groups are shown in Figure 5 A and Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We found 737 significantly downregulated genes in the AB uninjured group compared to the VEH uninjured group. These genes included regulators of skeletal development ( Alpl [ 37 ], Col6a1 [ 54 ], Col6a2 [ 55 ], Sox9 [ 37 ], Sox11 [ 56 ], and Wnt9a [ 57 ]), Hippo signaling ( Tead1 , Tead4 [ 58 ], and Yap1 [ 59 ]), muscle contraction ( Myh8 , Myh2 , and Myom2 ), and inflammatory response ( Tlr5 [ 60 ], Ccl8 [ 61 ], Cxcl13 [ 37 ], C5ar1 [ 62 ], Cxcr1 [ 63 ], and Foxo6 [ 64 ]). Inflammatory gene comparison between AB injured and uninjured groups compared to the corresponding VEH groups are shown in Figure 5 A and Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In Fu et al study [96], YAP, but not TAZ, was found to safeguard MSCs from cellular senescence as shown by KO experiments. Interestingly, YAP KO, but not TAZ, significantly increases the expression of Mlinc.28428.2.…”
Section: K-mers Analysis Of Markers In Functional Cell Situationmentioning
confidence: 88%
“…11 The pathogenesis of OA has been linked with the senescence of BMSCs while osteogenesis differentiation has been associated with the delay of the aging process, whereas adipogenic differentiation results in accelerated MSC aging process. 6,7 A recent study revealed that miR-27a-3p could promote the osteogenic differentiation of MSCs by targeting ATF3, thereby relieving OA symptoms. 31 In a word, miR-27b-3p may be a potentially promising regulator in the osteogenesis differentiation and adipogenic differentiation of BMSCs and also a vital mediator of OA.…”
Section: Discussionmentioning
confidence: 99%
“…5 The pathogenesis of OA has been speculated to be associated with the senescence of mesenchymal stem cells (MSCs). 6,7 A cell therapy method based on MSCs has been validated to be a promising OA treatment approach. 8 Accumulating data have indicated the significance of microRNAs (miRNAs) in the regulatory mechanisms associated with various inflammation-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%